Treatment of bifurcation lesions with two stents: one year angiographic and clinical follow up of crush versus T stenting. Issue 3 (17th June 2005) - Ge, L; Iakovou, I; Cosgrave, J; Agostoni, P; Airoldi, F; Sangiorgi, G M; Michev, I; Chieffo, A; Montorfano, M; Carlino, M; Corvaja, N; Colombo, A
Abstract : Objectives: To compare long term outcomes of the crush versus the T technique in bifurcation lesions. Design: 182 consecutive patients were identified who underwent percutaneous coronary interventions for bifurcation lesions with drug eluting stents between April 2002 and January 2004. Two techniques were used according to the operator's discretion: crush (group C, n = 121) or T (group T, n = 61). Results: In-hospital outcome differed significantly between the two groups. Angiographic follow up was available for 142 (78%) patients. Groups C and T did not differ significantly regarding late loss (0.42 (0.39) mm v 0.34 (0.35) mm, p = 0.52) and rate of restenosis (16.2% v 13.0%, p = 0.80) in both the main and the side branch without final kissing balloon post-dilatation. However, when final kissing balloon post-dilatation was performed, group C had significantly lower late lumen loss (0.23 (0.21) mm v 0.37 (0.33) mm, p = 0.02) and restenosis rate (8.6% v 26.5%, p = 0.04) in the side branch. At one year's clinical follow up, group C compared with group T had lower rates of target lesion revascularisation (14.0% v 31.1%, p = 0.01) and target vessel revascularisation (16.5% v 32.8%, p = 0.02). Conclusions: In non-selected bifurcation lesions treated with drug eluting stents, the restenosis rate remains relatively high in the side branch. Compared with the T stenting technique, crush stenting with kissing balloon post-dilatation is associated with a reduced rate of restenosis in the side branch.